Uwiedzeni przez manekiny, czyli o erotyce sztucznych ciał (na przykładzie opowiadania Płaszcz Józefa Olenina Eugéne’a Melchiora de Vogüégo) - Grażyna Gajewska (Przestrzenie Teorii)
n the article I shake a common conviction that the quasi-female mannequins fascinate us because they remind beautiful, real women in their unliving materiality they represent human bodies. Basing on psychoanalytical theories, I am proposing a thesis that in this fascination the representation of those alive (empirical) bodies is not meant, but a presentation of the aesthetic and especially erotic fantasies. The point of reference of this fascination is not a body of blood and bones, often imperfect, handicapped and ageing, but fantasies about the creation, embodiment, enlivening of the ideal woman whose symbol is the mythical Galatea sculpted by Pygmalion. The aesthetic-erotic fascination with mannequins is seen in many artworks and literary works. In this article I discover this phenomenon by analysing a fantastic story by Eugéne Melchior de Vogüé. However, the choice of this work does not mean that the fascination with the quasifeminine mannequins is exclusively a motif of fantastic prose. Just the opposite, for instance, it can be found in realistic novels like Emil Zola’s Ladies' Paradise, in which descriptions of mannequins in shop windows are saturated with erotic admiration connected with the category of luxury. However, due to the fact that fantastic literature is a particular field of play for fantasy and unconsciousness, this psychic energy being the consequence of the dramatised hallucination of displacing, my choice was Le manteau de Joseph Oléonine. Analysis of this work becomes a contribution to wider interpretations of the phenomenon of quasi-feminine mannequins in the West European culture of the turn of the 19th and 20th centuries.